Prevalence and impact of sarcopenia in non‐cirrhotic portal hypertension. (26th June 2019) - Lattanzi, Barbara; Gioia, Stefania; Di Cola, Simone; D'Ambrosio, Daria; Nardelli, Silvia; Tavano, Daniele; Farcomeni, Alessio; Merli, Manuela; Riggio, Oliviero
Abstract: Background & Aims: Little is known on nutritional parameters in patients with chronic portal vein thrombosis (PVT) and idiopathic non‐cirrhotic portal hypertension (INCPH). The study aims to assess the prevalence and the clinical impact of sarcopenia in patients with non‐cirrhotic portal hypertension (NCPH). A control group of cirrhotic patients was also studied. Both groups were followed up to establish the relationship between sarcopenia and clinical outcomes. Methods: Sixty‐seven patients with NCPH (51 PVT and 16 INCPH) were included in the study group and 104 patients with liver cirrhosis in the control group. The axial plane passing through the intersomatic disk between L3 and L4 was evaluated for the quantitative analysis of muscle mass and the skeletal muscle index (SMI) was calculated. The presence of sarcopenia was established according to SMI validated cut off. Results: Sarcopenia was present in the 38% of patients with INCPH, 35% of patients with chronic PVT, 32% of patients with compensated cirrhosis and 54% of decompensated cirrhotics. During a mean follow‐up of 51 ± 62 months, there was no difference in sarcopenic and non‐sarcopenic patients with NCPH for incidence of ascites, hepatic encephalopathy, esophageal varices, variceal bleeding and death. However, the incidence of refractory variceal bleeding requiring TIPS placement was significantly higher in comparison with the non‐sarcopenic ones (29% vs 7%, P  = 0.01 at log‐rank test). Conclusions: In patients with NCPH sarcopenia is similar to that observed in cirrhotic patients. Moreover, the rate of refractory variceal bleeding was higher in sarcopenic patients suggesting a clinical negative impact of muscle depletion.